Feasibility of computer-administered language assessment. - Brandone AC; Golinkoff RM; Hirsh-Pasek K (Perspectives on School-Based Issues, 2008)
The assessment of language in early childhood is essential for the early identification of children with special needs. However, administering traditional language assessments to large preschool populations can be prohibitively time-consuming and complicated. Thus, there is clear value in developing a standardized, norm-referenced, computer-administered language assessment battery that is both time-efficient and fun for children, that yields a meaningful profile of children's specific language competencies, and that can be administered by testers in a consistent manner without extensive training. Here we discuss research undertaken as part of an evaluation of the feasibility of developing such a language assessment tool for use with preschool children. Preschoolers (M = 3.60 years) were tested using a traditional, standardized language assessment (PLS-4) and a computer-administered task assessing (via the use of a touch-screen computer) verb vocabulary and comprehension of plural morphology, negation, and noun-verb agreement. All participants completed the entire test without difficulty. Moreover, analyses revealed significant correlations between performance on the computer-based language assessment, age, and performance on the PLS-4. These data support the notion that a computer-administered language assessment is methodologically feasible and can provide a practical and valid means by which to assess early language abilities.